Pengaruh Pendekatan Quantum Teaching dalam Meningkatkan Keaktifan dan Hasil Belajar Matematika Peserta Didik Di SMA Negeri 2 Gunungsitoli - Zendrato, Martalena Susanti; Mendrofa, Netti Kariani (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2023)
One of the problems in the mathematics learning process at SMA Negeri 2 Gunungsitoli is the low level of student engagement and suboptimal learning outcomes. This research aims to evaluate the impact of implementing the Quantum Teaching approach in enhancing students' engagement and mathematics learning outcomes at SMA Negeri 2 Gunungsitoli. The research methodology used is an experimental approach with a quantitative method. The instruments used include observation sheets, learning engagement questionnaires, and algebraic function derivative materials tests. The research sample consists of students from classes XI MIPA 3 and XI MIPA 2, selected through purposive sampling techniques. Data analysis was conducted using hypothesis testing with the t-test. The research results show that in the hypothesis testing regarding learning engagement, both based on observation data (t calculated = 3.707, t table = 1.995) and data from questionnaires (t calculated = 3.300, t table = 1.995), there is a significant influence of the Quantum Teaching approach in improving the learning engagement of mathematics students at SMA Negeri 2 Gunungsitoli. Furthermore, in the hypothesis testing regarding mathematics learning outcomes, a t-calculated value of 2.190 was obtained, which also exceeds the t-table value of 1.995, indicating that the Quantum Teaching approach has a significant impact on improving the mathematics learning outcomes of students at SMA Negeri 2 Gunungsitoli.